Penerapan Media Pembelajaran Laboratorium Virtual Berbasis PhET Pada Materi Larutan Asam Basa di SMA N 1 Likupang - Gracesela Tangka; Djefry Tani (Oxygenius Journal Of Chemistry Education, 2022)
The..purpose of this study was..to determine the..improvement..of student learning outcomes in..class XI MIA 1 at SMA N 1 Likupang on acid-base solution using a PhET-based virtual laboratory. This...research..is a..quantitative research using experimental..method using a one-group pretest-posttest design. The sample in this study was class XI MIA 1 as an experimental class..with a total of 30..students. Data collection was done by giving..a pretest before the learning process was carried out and a posttest after the learning process. The research..data obtained in the form of the difference between the..average..pretest..and..posttest values ​​in the experimental class is 45.3. The average pretest value is 40.7 while the average posttest value is 86. Before the one sample t test was..carried out, the normality test was first carried out and it was found that the data were normally distributed. then tested by t-test, the results obtained are tcount = 17.14 > ttable = 2.001. Thus, it..can be concluded that there is an..increase in student learning outcomes in the..application of PhET-based virtual laboratory learning media on acid-base solution material at SMA Negeri 1 Likupang.